Clínica analítica de las organizaciones : una propuesta conceptual (2018)
ABSTRACT: As a result of a qualitative study of hermeneutical type, we present a proposal for implementation in organizations of the clinical method. The basis of this work is a theoretical foundation on which we review some classic concepts underlying the ability to articulate the clinical and organizational fields. The clinical-analytical method is not exclusive to health and disease issues; conversely, it has been used in such diverse fields as law, sociology, pedagogy, among others. This method involves the decomposition of discourse into its constituent elements. If it is accepted that organizations are concretions of founding speeches (institutions) it will be accepted that the clinical-analytical method is relevant for its study and intervention. Furthermore, it is argued that also humans are constituted by institutions. Accepting these premises, it is possible to speak of a human management analytically orientated, based on a philosophy of integrative management, that provides spaces for individual and group verbalization. As a consequence, it is proposed that this human management of analytically orientated tends to enhance the development of human beings, groups and the organization itself.